Airfare Distribution by Trip Purpose. Issue 1 (2016) - Gosling, Geoffrey D.; Landau, Steven; Adler, Thomas; Fowler, Mark
Airfares are an important input to air travel demand forecasting and other analyses, but there is no readily available source of data on how airfares vary by trip purpose in any given market. This paper presents the results of an analysis of the distribution of airfares by trip purpose for U.S. domestic air trips. The analysis will be used for developing a procedure to estimate the average airfare by trip purpose in any given domestic air travel market. The analysis combines the results of a nationwide survey of air travelers who reported the details of their most recent domestic paid air trips with airfare data from the U.S. Department of Transportation's 10% airline origin and destination survey. This approach gave generic distributions of the airfare paid in any given market for business and personal trips, expressed as a ratio of the average airfare in that market for all paid trips, which can be obtained from the airline origin and destination survey data. The paper describes how the results of the analysis can be used to generate the distributions of airfares and average airfares for business and personal trips in any given market and discusses future research needed to confirm and expand the analysis results and procedure presented in the paper.